ANALISIS PENGGUNAAN BAHASA PROKEM PADA KALANGAN REMAJA TERHADAP ESKSISTENSI BAHASA INDONESIA - Pandiangan, Justina; Panjaitan, Siti Rafiqah Zahirah; Masitah; Cindy Ramayani; Hutagalung, Aleka Ganefi Azwan (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The issue raised in this study is the analysis of slang (prokem) language usage among teenagers and its impact on the sustainability of the Indonesian language. This research uses a qualitative descriptive method, with data sources consisting of everyday teenage speech, which is presumed to contain slang vocabulary. Data collection techniques include observation, recording, and passive listening. Data analysis is conducted through data reduction techniques. The results of the study show that the use of slang among teenagers has a negative impact on the sustainability of the Indonesian language as a national identity. The predominant use of slang among teenagers affects their understanding of the Indonesian language, especially in formal contexts that demand proper language use. The younger generation, expected to be the pillars of the nation's progress, is more familiar with slang, making them less capable of positioning themselves in situations that require the correct use of the Indonesian language.